Perfectionist Types in the English as a Foreign Language Teaching Profession in Russia - Kenneth Wang; Tatiana M. Permyakova; Marina S. Sheveleva (National Research University Higher School of Economics, 2019)
This study examines perfectionism in the English language teaching profession in Russia. The aims are threefold: 1) to use latent profile analysis (LPA) to classify English as a foreign language (EFL) teachers into different types of perfectionists; 2) to compare different types of perfectionists using depression-anxiety-stress indicators (DASS); 3) to study the link between perfectionism and the perception of one's professional teaching activity. We used convenience sampling by collecting data from 117 English teachers (5% males, 95% females; age range 20-64; M= 39; SD=12) with the Short Almost Perfect Scale (SAPS) and the Depression Anxiety Stress Scale-21 (DASS-21). LPA was conducted to determine the optimal number of types of individuals based on their SAPS profile. Three distinct classes of perfectionists were found (adaptive, maladaptive, non-perfectionists). 27% of the respondents fell into the category of maladaptive perfectionists with high scores on both the Standards and Discrepancy subscales. Teachers with higher Standards tend to be more aware of their perfectionism. Teachers who are less satisfied with their English proficiency tend to be more stressed at work. However, the results of the study did not indicate significant differences between the perfectionist types on anxiety, depression, and stress. The findings suggest the need to develop these scales further for measuring perfectionism in the teaching profession and in EFL teaching particularly.